Can an educational podcast improve the ability of parents of primary school children to assess the reliability of claims made about the benefits and harms of treatments: study protocol for a randomised controlled trial. Issue 1 (December 2017) - Semakula, Daniel; Nsangi, Allen; Oxman, Matt; Austvoll-Dahlgren, Astrid; Rosenbaum, Sarah; Kaseje, Margaret; Nyirazinyoye, Laetitia; Fretheim, Atle; Chalmers, Iain; Oxman, Andrew; Sewankambo, Nelson
Abstract Background Claims made about the effects of treatments are very common in the media and in the population more generally. The ability of individuals to understand and assess such claims can affect their decisions and health outcomes. Many people in both low- and high-income countries have inadequate aptitude to assess information about the effects of treatments. As part of the Informed Healthcare Choices project, we have prepared a series of podcast episodes to help improve people's ability to assess claims made about treatment effects. We will evaluate the effect of the Informed Healthcare Choices podcast on people's ability to assess claims made about the benefits and harms of treatments. Our study population will be parents of primary school children in schools with limited educational and financial resources in Uganda. Methods This will be a two-arm, parallel-group, individual-randomised trial. We will randomly allocate consenting participants who meet the inclusion criteria for the trial to either listen to nine episodes of the Informed Healthcare Choices podcast (intervention) or to listen to nine typical public service announcements about health issues (control). Each podcast includes a story about a treatment claim, a message about one key concept that we believe is important for people to be able to understand to assess treatment claims, an explanation of how that concept applies to the claim, and a second example illustrating the concept. We designed the Claim Evaluation Tools to measure people's ability to apply key concepts related to assessing claims made about the effects of treatments and making informed health care choices. The Claim Evaluation Tools that we will use include multiple-choice questions addressing each of the nine concepts covered by the podcast. Using the Claim Evaluation Tools, we will measure two primary outcomes: (1) the proportion that 'pass', based on an absolute standard and (2) the average score. Discussion As far as we are aware this is the first randomised trial to assess the use of mass media to promote understanding of the key concepts needed to judge claims made about the effects of treatments. Trial registration Pan African Clinical Trials Registry, PACTR201606001676150. Registered on 12 June 2016.http://www.pactr.org/ATMWeb/appmanager/atm/atmregistry?dar=true&tNo=PACTR201606001676150 .